International spillovers of social challenges as a result of sanctions against Russia: An evaluation of the Azerbaijani case - Ibrahim Niftiyev (Proceedings book, 2022)
Since February 2022, a new phase of the war between Russia and Ukraine has begun. Apart from the direct consequences for Russia and Ukraine, all post-Soviet countries are affected, as Western sanctions against Russia significantly limit the economic development and cooperation prospects of the post-Soviet region. Azerbaijan is one of Russia's most important trading partners and a neighboring country, and there are serious concerns that these sanctions could have a negative impact on Azerbaijan's socioeconomic life. This is mainly because domestic production in Russia has declined, agricultural exports have been curtailed, and trade and transportation routes have been disrupted. Against the background of all these factors, the social impact of this situation seems to be dramatic. Therefore, this article analyzes qualitative data from social media and websites dealing with Azerbaijan's social challenges. To this end, expert opinions were analyzed using the thematic analysis method to examine the social impact of sanctions at three levels: people living abroad (migrants or expats), remittances, and the purchasing power of locals. The results show that there is a high expectation among experts that sanctions could have a negative impact on remittance flows from Russia to Azerbaijan due to the devalued Russian ruble. There is also a possibility that migrants working and living in Russia will return to Azerbaijan in greater numbers. Finally, experts agreed that the purchasing power of locals in Azerbaijan has declined due to sharp price increases that followed the production slump and export restrictions in Russia. These findings could support ongoing preparations for new socioeconomic realities in Azerbaijan as a result of Western sanctions against Russia. Now policymakers must develop a plan to quickly address Azerbaijan's social problems, even if it is not an emergency.
Conference: 8th International Conference on Economics and Social Sciences, Antalya, Turkey, 21-23 October 2022
Keywords: 330; Azerbaijani economy; expert opinion; Russia; sanctions; social impacts; thematic analysis